Numerical investigation of synthetic jets driven by thermoacoustic standing waves. (January 2020) - Chen, Geng; Krishan, Gopal; Yang, Yi; Tang, Lihua; Mace, Brian
Highlights: A thermoacoustically-driven synthetic jet actuator is proposed. Linear instability of the actuator is investigated using both network and CFD methods. The formation of a clear synthetic jet is identified through CFD simulations. The effects of key geometry parameters on the onset characteristics are studied. Abstract: We have carried out a preliminary study of the physical processes leading to the formation of a jet into external quiescent surroundings driven by thermoacoustic standing waves. The standing waves are initiated in a thermoacoustic engine (TAE) utilizing the thermoacoustic effect, and the synthetic jet is produced via a jet ejector where a sudden change in the cross-section is employed. We investigate the characteristics of the proposed synthetic jet actuator using both reduced-order network model and computational fluid dynamics (CFD) simulations. The network technique, which is based on linear thermoacoustic theory, can predict the onset of thermoacoustic instability in the frequency domain. The CFD code solves the fully coupled nonlinear compressible flow equations and enables the time-domain analysis of complex flow patterns, which facilitates comprehension of the jet formation process. Both theoretical analysis and numerical simulations reveal that spontaneous, self-excited oscillations inside the TAE will happen when the temperature ratio is greater than the onset temperature ratio for thermoacoustic instability. CFD simulations further identified the transition from no jet to a clear synthetic jet, which determines the onset temperature ratio for jet formation and the threshold value of a non-dimensional parameter. Finally, we carried out a parametric study to investigate the influence of resonator length and orifice diameter on the onset characteristics as well as other performance parameters including the acoustic intensity, space-averaged mean momentum flux, space-averaged velocity and the jet effectiveness. The proposed thermoacoustically-driven synthetic jet actuator may outperform conventional actuators driven by a piston, loudspeaker or piezoelectric transducers on occasions where the surface temperature is high, and therefore has the potential to be utilized for self-cooling purposes.